(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2020)
Utilization of soy waste as a ruminant feed is low due to storage problems and transportation costs. An experiment was carried out with fifteen goats to assess the feeding value of Napier grass (Pennisetum purpureum) ensiled with or without soy waste. Grass ensiled without soy waste was termed as NM silage, while grass ensiled 30% soy waste (w/w) was termed as NMS silage. In both silages, 1.0% molasses (w/w) were incorporated to enhance the fermentation process. After 2 months of ensiling, three diets were formulated and assigned to one of three groups: (i) Napier grass ad libitum plus 1% pellet of body weight (BW) on a dry matter (DM) basis (T1), (ii) NM silage ad libitum plus 1% soy waste of BW on a DM basis (T2), and (iii) NMS silage ad libitum (T3). The NMS silage showed a lower pH (4.04 vs. 4.64) than NM silage. The NMS silage exhibited higher proportions of DM, organic matter (OM), and crude protein (CP) compared to NM silage. Animals received T1 diet showed higher (p<0.05) DM, OM and neutral detergent fibre intake compared to the animals received T2 and T3 diets. However, animals received T2 diet showed higher CP intake than the animals received T1 and T3 diets. Similarly, animals received T2 diet showed higher (p<0.05) BW gain (49.4 vs. 16.5 g/d) than the goats fed T3 diet. In conclusion, the T3 diet may have limited goat performance, which needs further study to improve the quality of silage.